Konsep Mahabbah pada Mapel Pendidikan Agama Islam sebagai Solusi Mengatasi Trauma Belajar pada Anak - Ifham Choli; Syarifah Soraya; Etika Nailur Rahma (Universitas Indraprasta PGRI, 2025)
Learning trauma in children often arises from negative experiences in the educational process, such as academic pressure, monotonous teaching methods, or a lack of emotional engagement from teachers. This has implications for decreased motivation, self-confidence, and even a rejection of learning activities. In the context of Islamic Religious Education, the concept of mahabbah or love can be a strategic solution to overcome these problems. Mahabbah is understood as the foundation of affection, respect, and care instilled by teachers in learning interactions. Through this approach, learning is not only oriented towards cognitive aspects, but also touches the affective and psychomotor domains, so that children feel accepted, appreciated, and loved. This study aims to explore the role of the mahabbah concept in creating a humanistic, enjoyable, and calming learning atmosphere for children who experience learning trauma. This research method uses a qualitative case study approach. The results of the study indicate that the implementation of mahabbah in Islamic Religious Education subjects can foster a sense of security, build emotional closeness between teachers and students, and restore children's enthusiasm for learning.